When Should I Rotate? Clerkship Timing of Students Who Successfully Match in OBGYN - Dotters-Katz, Sarah K.; Schroeder, Brooke; Rusk, Debra; Avery, Lori; Sutton, Jill M.; Hou, Melody Y.; Shanks, Anthony (American Journal of Perinatology, 2025)
Medical students are routinely advised to rotate into their specialty of interest later in the year, likely to gain clinical experience, improve their clerkship performance, and therefore garner positive recommendations or performance reviews. However, there is little research to support this guidance. This study aims to examine a large multi-institutional cohort of students who matched into obstetrician and gynecologist (OBGYN) programs, to determine if there are any differences in match rates based on rotation timing.In this IRB-approved retrospective cohort study, we included 204 students who matched in OBGYN from five geographically diverse medical schools between 2019 and 2023. The academic year was divided into trimesters due to varied rotation lengths among schools. We utilized bivariate statistics and regression models to examine the percentage of students matching in each trimester, as well as the percentage of students rotating during the first block of the academic year.After controlling for race and gender identity, there was no significant difference in match rates for OBGYN between those who rotated early in the clerkship year and those who rotated later. Students from schools without choice in timing were more likely to rotate in the first trimester.For this cohort, there is no difference in match rates into OBGYN based on the timing of their core rotation.
Keywords: residency match; clerkship timing; rotation timing; OBGYN